Technical and economical assessment of distributed electrochemical storages for load shifting applications: An Italian case study. (May 2016) - Graditi, G.; Ippolito, M.G.; Telaretti, E.; Zizzo, G.
Abstract: Time-of-use (TOU) energy cost management involves the use of energy storage systems (ESSs) by customers to reduce their electricity bills. The ESS is charged during off-peak time periods, when electricity energy prices are low, and discharged during times when on-peak energy prices are applied. This article addresses the question whether it is economically viable to install medium-scale distributed ESSs designed to lower the electricity cost for a customer-side application, assuming flexible electricity tariffs. The technical/economical evaluation is carried out referring to lithium-ion (Li-ion), sodium sulfur (NaS) and vanadium redox battery (VRB) technologies, performing a parametric analysis by changing the capital cost of the batteries and the difference between the maximum and minimum electricity price. A case study is performed to show the advantages/disadvantages of the proposed approach. The analysis reveals that, at the current costs of ESSs, the use of batteries for TOU applications is economically advantageous for a public institution facility in Italy only if there is a significant difference between the maximum and the minimum electricity price. The decrease in the cost of storage, stimulated by the implementation of support policies, will make ESS even more convenient for load shifting applications.